(untitled) (Annals of the Institute of Biology, 2023)
Online teaching has changed the dynamics of students' work and led to a series of changes concerning student engagement, motivation and academic success. The main goal of this research was to analyze the success of students from the Department of Biology at the Faculty of Science in Sarajevo during online classes compared to traditional classes, and to assess their motivation in online classes. Independent samples t-test, descriptive statistics and one-way ANOVA were used for data analysis and coding. The impact of online teaching on student success was assessed by comparing the average grades in subjects from the first and second year of study during online and face-to-face teaching. In the academic year 2018/2019, 79 students attended the first year of study, and 66 students attended in 2020/2021. For the second year of study, 74 students attended in the 2018/2019 academic year, while 90 students attended in 2020/2021. From the third and fourth year of study 64 students took part in in the questionnaire to assess motivation. The results showed that online teaching had a positive impact on the academic success of students with a statistically significant difference in the success achieved during online and face-to-face teaching. The research showed that students have a neutral academic motivation and a high degree of cooperation with professors and colleagues, with a significant difference between years of study.